The Role of the Business Intelligence System in Enhancing High Performance: An Exploratory Study of a Sample of Private Banks in Erbil Governorate - Nasser, Bushra; Ali, Huda (The Arab Journal of Administration, 2020)
The research dealt with the subject of the system of business intelligence and its role in promoting high performance and tested in the banking sector represented by eight banking in Erbil. The research was conducted on a sample of (80) managers distributed at different administrative levels (members of the board of directors, managers sections of the people of the directors of office), a questionnaire was used as a tool for key data collection and information, has sought search to test the hypothesis main effect that measure relationship effects between depending on the result extracted from the neural network in order to answer questions related to the problem of search, it was a set of conclusions perhaps the most important that the system intelligent business system of a vital whatever the success of organizations persistence and contribute to enhance performance, this was confirmed by the results of analysis showed that there is a significant relationship between the components of the system of business intelligence and the dimension of high performance, based on this, a set of recommendations was developed, the most important of which is the need to improve the skills of officials in the banks surveyed to deal with the huge amount of information and at all levels, thus contributing to achieving high performance and speed up work and achieve better.